Los registros de salud personal: el caso de la Carpeta Personal de Salud de Cataluña Personal health records: the case of the Personal Health Folder of Catalonia (Spain) - Francesc Saigí; Ismael Cerdá Calafat; Joan Guanyabens Calvet; Elisenda Carrau Vidal (Elsevier, 2012)
Este trabajo explora las posibilidades de la Carpeta Personal de Salud e identifica la brecha entre el potencial de esta herramienta y las aplicaciones que ofrece a través de Internet. Se presenta la Carpeta Personal de Salud, un proyecto vinculado a la Historia Clínica Compartida de Cataluña, que ofrece un punto de acceso a la información sobre la propia salud que es seguro, personalizado y soportado por las tecnologías de la información y la comunicación. La experiencia, realizada íntegramente por la Consejería de Salud de la Generalitat de Cataluña, escogió una metodología mediante encuesta anónima. Los resultados han sido de gran relevancia para obtener información sobre la idoneidad de los datos publicados y las expectativas de una herramienta dirigida a la población en general. The aims of this study were to explore the possibilities of the Personal Health Folder and to identify the gap between the potential applications of this tool and what it offers through the Internet. The Personal Health Folder is presented, a project linked to the Shared Medical Record of Catalonia (Spain), which provides citizens with an access point to information about their health insurance, customized and supported by information and communication technologies. The project was carried out by the Ministry of Health of the Government of Catalonia (Generalitat de Catalunya) and data were gathered through an anonymous survey. The results were critical to obtain information on the suitability of the published data and on the expectations of a tool aimed at the general population.